Rethinking diversity frameworks in higher education - Chun, Edna Breinig; Feagin, Joe R. (New York, NY : Routledge, 2020)
"The book offers concrete approaches, concepts, and tools that will enable higher education leaders to identify, address, and counteract persistent structural and behavioral barriers to inclusion. As such, it shares a series of practical recommendations that will assist presidents, provosts, executive officers, boards of trustees, faculty, administrators, diversity officers, human resource leaders, diversity taskforces, and researchers as they seek to implement comprehensive strategies that result in sustained diversity change"--
Campus turmoil : the "new normal" of racist speech and actions -- Discriminatory experiences from academic frontlines : limits of organizational and legal redress -- Questioning "implicit bias" and "microaggressions" : toward better terminology and concepts -- Reformulating the concept of "microaggressions" : everyday discrimination in academia -- Imposed racial identities : another essential concept -- Resisting and coping with everyday discrimination -- Moving forward : issues, strategies, and recommended solutions.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed on January 20, 2023).
Edna B. Chun is an educational leader and award-winning author with more than two decades of strategic human resource and diversity leadership experience in higher education. Among her co-authored books are Leading a Diversity Culture Shift in Higher Education (Routledge 2018) and The Department Chair as Transformative Diversity Leader (Stylus 2015). She currently serves as Chief Learning Officer for HigherEd Talent, a national diversity and human resources consulting firm. Joe R. Feagin is Distinguished Professor at Texas A & M University. Among his books are Systemic Racism (Routledge 2006) and (with Kimberley Ducey) Racist America (4th edn, Routledge 2019). He is the recipient of the American Association for Affirmative Action's Fletcher Lifetime Achievement Award and the American Sociological Association's W.E.B. Du Bois Career of Distinguished Scholarship Award. He was the 1999-2000 president of the American Sociological Association.
eBooks on EBSCOhost
Keywords: Discrimination in higher education; Educational equalization; Educational leadership; Inclusive education; Educational change; Mainstreaming in education; School improvement programs; Discrimination dans l'enseignement supérieur.; Démocratisation de l'enseignement.; Leadership en éducation.; Intégration scolaire; Enseignement -- Réforme.; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Sociology -- General; School improvement programs; Mainstreaming in education; Discrimination in higher education; Educational change; Educational equalization; Educational leadership; Inclusive education